2015
DOI: 10.14814/phy2.12551
|View full text |Cite
|
Sign up to set email alerts
|

Vascular, but not luminal, activation of FFAR1 (GPR40) stimulates GLP-1 secretion from isolated perfused rat small intestine

Abstract: Glucagon-like peptide 1 (GLP-1) plays a central role in modern treatment of type 2 diabetes (T2DM) in the form of GLP-1 enhancers and GLP-1 mimetics. An alternative treatment strategy is to stimulate endogenous GLP-1 secretion from enteroendocrine L cells using a targeted approach. The G-protein-coupled receptor, FFAR1 (previously GPR40), expressed on L cells and activated by long-chain fatty acids (LCFAs) is a potential target. A link between FFAR1 activation and GLP-1 secretion has been demonstrated in cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 66 publications
4
63
0
Order By: Relevance
“…2,13 Interestingly, however, a recent study found that while LCFAs do stimulate GLP-1 release from the rat small intestine, this was only observed when the LCFA was administered via the vasculature and not when administered via the intestinal lumen. 146 Although a limited observation from a single study, this surprising result suggests a need to absorb the LCFA in order to produce the effect on GLP-1 release. If confirmed, this is likely to have significant implications as to how FFA1 functions as a nutrient sensor and, indeed, if and how it will be possible to manipulate FFA1 function through diet.…”
Section: Lcfas At Ffa1mentioning
confidence: 99%
“…2,13 Interestingly, however, a recent study found that while LCFAs do stimulate GLP-1 release from the rat small intestine, this was only observed when the LCFA was administered via the vasculature and not when administered via the intestinal lumen. 146 Although a limited observation from a single study, this surprising result suggests a need to absorb the LCFA in order to produce the effect on GLP-1 release. If confirmed, this is likely to have significant implications as to how FFA1 functions as a nutrient sensor and, indeed, if and how it will be possible to manipulate FFA1 function through diet.…”
Section: Lcfas At Ffa1mentioning
confidence: 99%
“…Detection of ingested fat, by contrast, seems to largely depend on G-protein-coupled receptors (GPRs) that detect the triacylglycerol digestion products, fatty acids (sensed by GPR40 and GPR120), and monoacylglycerols (sensed by GPR119) (60). Of note, GPR40-dependent fatty acid detection by L cells also seems to depend on the rate of nutrient absorption, as intestinal perfusion experiments have indicated that the receptor is accessible from the basolateral rather than luminal direction (67). Although close apposition of enteroendocrine cells with the terminals of enteric neurons has been described, the physiological role of neuronal signals in regulating gut hormone secretion remains uncertain (15).…”
Section: Gut Endocrine Regulation Of Glucose Metabolismmentioning
confidence: 99%
“…3,33 For example, a free fatty acid receptor 1 (FFAR1) agonist did not affect intestinal secretory functions when administered intraluminally, but induced GLP-1 release after intravascular administration. While we did not evaluate the systemic effect of MSG and MSG plus IMP, absorption of nutrients can have stimulatory effects via the vasculature that differs from direct interaction in the gut lumen.…”
Section: Activation Of T1r1/t1r3 Receptors Stimulate Gα I2 Protein mentioning
confidence: 99%